THOUGHTS ON THE THEORY AND LANGUAGE OF ARCHITECTURE - Azzaiddy Abdullah, editor 655297; Norwina Mohd. Nawi, editor 655298; Shireen Jahn Kassim, editor 204684 (Kuala Lumpur : Kulliyyah of Architecture and Environmental Design, 2009)
Includes indexes.